The Influence of Product Quality and Service Quality on Repurchase Intentions at Waroeng Steak & Shake - Riyanto; Taryono; Sutrisno (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study examines the influence of product quality and service quality on consumers’ repurchase intention at Waroeng Steak & Shake. In the increasingly competitive culinary industry, repeat purchase behavior is essential for maintaining customer loyalty and business sustainability. This quantitative study used primary data collected through structured questionnaires distributed to 195 respondents who had purchased from the restaurant within the last three months. The data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that both product quality and service quality have a positive and significant effect on repurchase intention, both partially and simultaneously. Product aspects such as taste consistency and food presentation strongly influence consumers’ willingness to repurchase, while responsive and reliable service also contributes significantly. The study highlights the importance of maintaining product consistency and service excellence to strengthen customer retention in the culinary business sector